Ultrasonic-assisted gamma-aminobutyric acid crystal particle size regulation and control method
By employing an ultrasound-assisted γ-aminobutyric acid (GABA) crystallization method, combined with the ultrasonic cavitation effect and gradient cooling strategy, we have achieved particle size refinement, narrowing of distribution, and inhibition of agglomeration of GABA crystals. This solves the problems in existing technologies, improves the quality of crystal products and process efficiency, and is suitable for high-end formulations.
Patent Information
- Application Number
- CN202511453089.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-13
- Publication Date
- 2025-11-11
- Estimated Expiration
- 2045-10-13
AI Technical Summary
Existing technologies cannot simultaneously achieve particle size refinement, narrowing of distribution, and agglomeration inhibition of γ-aminobutyric acid crystals, and the stability of crystal form is difficult to guarantee, which limits its application in high-end formulations.
An ultrasound-assisted γ-aminobutyric acid (GABA) crystallization method was adopted, which included raw material pretreatment, evaporation concentration-ultrasound-cooling coupled crystallization, aging and post-treatment. By reducing the nucleation barrier through the ultrasonic cavitation effect, combined with precise control of supersaturation and gradient cooling strategy, particle size refinement, narrowing of distribution and agglomeration inhibition were achieved.
This method achieves the refinement of γ-aminobutyric acid crystal particle size to ≤200μm and narrowing of distribution span to ≤1.5, thereby breaking hydrogen bond adhesion, inhibiting aggregation, ensuring crystal stability, improving crystal product quality and process efficiency, and meeting the needs of high-end formulations.
Smart Images

Figure CN120919673A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of amino acid crystallization technology, and in particular to a method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization. Background Technology
[0002] Gamma-aminobutyric acid (GABA) is a naturally occurring non-protein amino acid. As a major inhibitory neurotransmitter in the mammalian central nervous system, it exhibits clear physiological activities in areas such as nerve sedation, anti-anxiety effects, and cardiovascular function regulation, and is therefore widely used in pharmaceuticals and functional foods. In pharmaceutical formulations, the crystal quality of GABA (e.g., particle size distribution, crystal integrity) directly affects the dissolution rate, bioavailability, and subsequent processing properties of the formulation (LMBelca, M. Krajnc. The use of ultrasound in the crystallization process of an active pharmaceutical ingredient, Ultrason. Sonochem. 58 (2019) 104642; L. d. LS Castillo-Peinado, MD Luque deCastro. The role of ultrasound in pharmaceutical production: sonocrystallization, J. Pharm. Pharmacol. 68 (2016) 1249–1267; PH Zhao, BS Liu, CX Xie, QJ Li, X. Du, H. Sun. Crystallization of citicoline sodium by anti-solvent assisted with ultrasound, J. Cryst. Growth. 593 (2022) 126738). Smaller crystal particle size can provide a larger specific surface area, thereby accelerating the dissolution rate of the drug and improving the absorption efficiency of the human body; while a narrower single-peak distribution can ensure the consistency of drug dissolution and the uniformity of tablet compression. Therefore, as a key step in the separation and purification of γ-aminobutyric acid, the optimization of the crystallization process is crucial for improving product quality.
[0003] However, the γ-aminobutyric acid molecule contains a strong hydrogen bond network (mainly formed by the interaction between amino and carboxyl groups), which makes it easy to form layered aggregates and cause severe agglomeration during traditional crystallization. This is characterized by a generally large median particle size (Dv50) and a wide particle size distribution. Furthermore, the agglomeration phenomenon leads to particle adhesion and stacking, which seriously restricts subsequent formulation processing (such as dissolution, mixing, and tableting) and the exertion of drug efficacy.
[0004] Currently, the crystallization of γ-aminobutyric acid (GABA) mainly relies on traditional processes, which have significant limitations. Dissolution crystallization requires the addition of a miscible antisolvent to the GABA solution to reduce solubility by altering the solvent composition; however, fluctuations in solvent composition easily lead to uneven crystal morphology and consume large amounts of antisolvent. Evaporation crystallization relies on solvent removal to increase concentration, which is energy-intensive and makes precise control of crystal particle size difficult. Cooling crystallization induces crystallization through temperature gradients; uneven cooling rates easily induce secondary nucleation, further exacerbating the dispersion of particle size distribution (increased DS value) and the degree of agglomeration.
[0005] To address the aforementioned issues, ultrasound technology has been increasingly applied to crystal regulation. Through cavitation (bubble collapse generating localized high temperature and pressure), acoustic flow (enhanced mass transfer), and interfacial energy modulation, it can reduce solid-liquid interfacial tension, promote uniform nucleation, and disrupt interparticle hydrogen bonds to inhibit aggregation. This technology has been proven effective in refining particle size and narrowing distribution in the crystallization of compounds such as sodium cytidine diphosphate choline. However, key bottlenecks remain in ultrasound-assisted crystallization research on GABA: the response mechanism of the strong intermolecular hydrogen bond network of GABA to the ultrasound cavitation effect is not yet clear, making it difficult to establish targeted regulation models; and systematic research is lacking on the synergistic optimization of ultrasound intervention timing (e.g., metastable region triggering nodes), energy input modes (e.g., power, duration of action), and evaporation-cooling processes. Therefore, current technologies cannot simultaneously achieve multi-objective synergistic regulation of γ-aminobutyric acid (GABA) particle size refinement (Dv50 < 200 μm), distribution narrowing (DS < 1.5), aggregation inhibition, and crystal form stability, limiting its application in high-end formulations.
[0006] Therefore, developing an ultrasound-assisted process that can precisely control the crystal size of GABA, especially achieving breakthroughs in both narrowing the distribution and inhibiting aggregation, while maintaining crystal stability, has become the key to overcoming existing technological bottlenecks and is of great significance to promoting the development of amino acid drug crystallization technology. Summary of the Invention
[0007] The technical problem to be solved by the present invention is to provide a method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization.
[0008] The technical solution adopted in this invention is: A method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid (GABA) crystallization involves removing impurities and decolorizing a γ-aminobutyric acid-containing solution, heating and stirring to concentrate it to near saturation, then performing ultrasound-assisted crystallization, cooling, aging, and filtration to obtain coarse crystals. Finally, the solution is washed and dried to obtain the target crystals. The specific steps are as follows: (1) Impurity removal and decolorization: The liquid containing γ-aminobutyric acid is removed and decolorized, and the filtrate is collected as the solution to be concentrated; (2) Heating and concentration: The filtrate is placed in a crystallizer and heated and stirred to concentrate it to near saturation; (3) Ultrasonic-assisted crystallization: When the filtrate is concentrated to near saturation, turn on ultrasonic-assisted crystallization, continue heating and stirring to evaporate until the crystal precipitation rate reaches 50% (based on the volume of saturated filtrate), then stop evaporation, and then cool it to 20-25℃ at a cooling rate of 0.4-0.6℃ / min. Stop the ultrasonic and stirring action, and continue aging for 60-120 min to obtain the crystal mother liquor; (4) Washing and drying: filter the mother liquor to obtain crude crystals, wash the crystals, and dry them to obtain γ-aminobutyric acid crystals.
[0009] Preferably, in the above-mentioned ultrasonic-assisted γ-aminobutyric acid crystallization particle size control method, the heating and concentration conditions in step (2) and the heating, stirring and evaporation conditions in step (3) are: temperature 60-75℃, vacuum degree 0.07-0.09MPa, and stirring speed 250-450r / min.
[0010] Preferably, in the above-mentioned method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization, the heating and concentration conditions / heating and stirring evaporation conditions are: temperature 65-70℃, vacuum degree 0.08MPa, and stirring speed 300r / min.
[0011] Preferably, in the above-mentioned method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization, the cooling rate is 0.5℃ / min.
[0012] Preferably, in the above-mentioned ultrasonic-assisted γ-aminobutyric acid crystallization particle size control method, the crystal aging time after cooling in step (3) is 90 min.
[0013] Preferably, in the above-mentioned method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization, the conditions for ultrasound-assisted crystallization in step (3) are as follows: the ultrasound power density is 20-30 W / L (lower power can avoid excessive crystal breakage, synergistically inhibit agglomeration and maintain narrow distribution), the ultrasound probe is inserted to a depth of 1 / 3 to 1 / 2 below the surface of the crystal slurry (based on the effective volume of the crystallizer), and an intermittent ultrasound mode is used.
[0014] Preferably, in the above-mentioned method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization, the ultrasonic power density is 24.4 W / L.
[0015] Preferably, in the above-mentioned method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization, the intermittent ultrasound mode is a pause of 8-16 seconds after every 2-4 seconds of ultrasound (to avoid excessive particle breakage and agglomeration caused by continuous ultrasound).
[0016] Preferably, in the above-mentioned method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization, the ultrasound probe is inserted to a depth of 1 / 3 below the surface of the crystal slurry (based on the effective volume of the crystallizer), and an intermittent ultrasound mode is adopted, with a 12-second pause after every 3 seconds of ultrasound.
[0017] The beneficial effects of this invention are: The described ultrasonic-assisted γ-aminobutyric acid (GABA) crystallization particle size control method utilizes a synergistic process of raw material pretreatment, evaporation and concentration-ultrasonic-cooling coupled crystallization, aging, and post-treatment. By leveraging the ultrasonic cavitation effect to lower the nucleation barrier and combining precise supersaturation control with a gradient cooling strategy, it achieves refined GABA crystal particle size, significantly narrowed crystal distribution, and effective suppression of agglomeration. Simultaneously, it ensures crystal stability, resulting in complete and smooth crystals, significantly improving crystal product quality and process efficiency, and possesses significant industrial application value. Specifically, this is reflected in: (1) Achieving a synergistic breakthrough in particle size refinement, distribution narrowing and agglomeration inhibition. In traditional processes, particle size Dv50 > 500 μm, distribution span (DS) > 2.0 (wide bimodal distribution), and severe agglomeration (particle adhesion and stacking) are observed. This invention controls the median particle size (Dv50) of GABA crystals to ≤ 200 μm and significantly narrows the particle size distribution span (DS) to ≤ 1.5 (narrow unimodal distribution) through ultrasonic synergistic regulation. At the same time, it effectively breaks hydrogen bond adhesion and inhibits agglomeration, achieving synergistic optimization of "particle size refinement + distribution narrowing + agglomeration inhibition", and fundamentally solving the core pain points of uneven dissolution and poor flowability of formulations. (2) The process efficiency and controllability are significantly improved, and key parameters such as ultrasonic power and cooling rate can be quantitatively controlled, providing a generalizable paradigm for similar amino acid crystallization processes; (3) It ensures the stability of crystal form and functional groups. X-ray diffraction (XRD) and infrared spectroscopy analysis confirmed that the crystal form did not change before and after ultrasonic treatment. Scanning electron microscopy (SEM) results showed that the crystal morphology was complete and the surface was smooth. After agglomeration inhibition, the particle dispersibility was significantly improved, ensuring product quality consistency and meeting the needs of high-end formulation development. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the ultrasonic-assisted GABA crystallization experimental apparatus. In the diagram, 1-ultrasonic generator, 2-light intensity recorder, 3-photoelectric transformer, 4-magnetic stirrer controller, 5-laser generator, 6-laser power supply, 7-high and low temperature cycle temperature controller, 8-ultrasonic probe, 9-thermometer, 10-magnetic rotor, 11-jacketed crystallizer. Figure 2 This is a graph showing the effect of stirring speed on particle size distribution. Figure 3 This is a graph showing the effect of cooling rate on particle size distribution. Figure 4 The graph shows the effect of ultrasonic power density on crystal habit, where a. 19.4 W / L, b. 30.9 W / L, c. 40.5 W / L, d. 51.6 W / L, e. 82.4 W / L; Figure 5 The diagram shows the effect of aging time on crystal habit, where a. 30 min, b. 60 min, c. 90 min, d. 120 min; Figure 6 A comparison diagram of GABA particle size distribution before and after optimization; Figure 7 To optimize the XRD patterns of GABA crystals before and after processing; Figure 8 To optimize the infrared spectra of GABA before and after; Figure 9 The SEM images of GABA before and after optimization are shown, where (a) is before optimization and (b) is after optimization. Detailed Implementation
[0019] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0020] Unless otherwise specified, the raw materials used in the embodiments of this application are all purchased commercially and used directly without any special treatment.
[0021] Unless otherwise specified, the analytical methods in the embodiments all adopt conventional instrument or equipment settings and conventional analytical methods.
[0022] Example 1 Ultrasonic-assisted GABA crystallization experimental apparatus The GABA crystallization experimental apparatus provided by this invention is as follows: Figure 1The apparatus, as shown, includes an ultrasonic generator 1, a light intensity recorder 2, a photoelectric transformer 3, a magnetic stirrer 4, a laser generator 5, a laser power supply 6, a high and low temperature cycle controller 7, an ultrasonic probe 8, a thermometer 9, a magnetic rotor 10, and a jacketed crystallizer 11. The experimental setup centers on the jacketed crystallizer 11 (the core reaction vessel, which carries the GABA solution and performs concentration, crystallization, and other reactions). The magnetic rotor 10 is placed at the bottom of the jacketed crystallizer 11, and the magnetic stirrer 4 is horizontally positioned below it, directly below the magnetic rotor 10. During operation, the magnetic stirrer 4 is submerged in the solution within the jacketed crystallizer 11, and drives the rotor to rotate via a magnetic field. The thermometer 9 and the ultrasonic probe 8 are both suspended within the jacketed crystallizer 11. One end of the thermometer 9 is inserted into the solution within the jacketed crystallizer 11, while the other end is exposed for temperature measurement. One end of the ultrasonic probe 8 is inserted into the crystal slurry within the jacketed crystallizer 11 at a depth of 1 / 3 to 1 / 2. The ultrasonic generator 1, located on the side of the jacketed crystallizer 11, is connected to the other end of the crystallizer 11 via a wire. The high and low temperature circulating temperature controller 7 is located on the side or below the jacketed crystallizer 11 and is connected to the jacket around the outer periphery of the jacketed crystallizer 11 via a pipe to realize the circulation of the temperature control medium. The laser generator 5 and the light intensity recorder 2 are horizontally and symmetrically arranged on both sides of the jacketed crystallizer 11. The laser emission port of the laser generator 5 and the recorder receiving port of the light intensity recorder 2 are aligned at the same height. The laser generator 5 is electrically connected to the laser power supply 6, and the light intensity recorder 2 is electrically connected to the photoelectric transformer 3, forming a complete particle size monitoring channel for particle size monitoring.
[0023] Example 2 Investigating the effect of stirring speed on the crystallization of γ-aminobutyric acid After impurity removal and decolorization, the filtrate was transferred to a jacketed crystallizer and concentrated to near saturation at 70℃, 0.08MPa, and arbitrary speed. Immediately, ultrasonic-assisted crystallization was started at 24.4W / L power in an intermittent mode of "ultrasonic 3s pause 12s," with the magnetic stirrer speed adjusted as a variable until the crystal precipitation rate reached 50% (based on the volume of saturated filtrate). Evaporation was then stopped, and the crystals were gradually cooled to 25℃ at a cooling rate of 0.5℃ / min. Ultrasonic aging was then paused, and the crystals were aged for 90 minutes. The crystal slurry was then separated by vacuum filtration, and the crystals were washed with 95% ethanol. The crystals were then vacuum dried at 60℃ and 0.08MPa for 3–5 hours to constant weight. Finally, the particle size, distribution, and crystal morphology of the dried crystals were characterized by a laser particle size analyzer and a scanning electron microscope to obtain the crystallization results under different stirring speeds.
[0024] The effect of stirring speed on particle size distribution was studied under the following conditions: evaporation temperature 70℃, ultrasonic power 24.4 W / L, ultrasonic 3s pause 12s, cooling rate 0.5℃ / min, and aging time 90 min. (Table 1 and...) Figure 2The particle size and distribution of crystals under different stirring speeds are shown.
[0025] The experimental results at different stirring speeds are shown in Table 1. Table 1 shows that with increasing stirring speed, the Dv50 of the crystals decreases, and the surface area average particle size D[3,2] and volume average particle size D[4,3] also decrease accordingly. This trend weakens when the stirring speed exceeds 300 r / min. DS also decreases with increasing stirring speed, but when the stirring speed increases to 500 r / min, DS increases significantly. Figure 2 It can be seen that when the stirring speed is 100 r / min, the particle size distribution is wide and the crystal size is relatively large. This is because the mass transfer is insufficient at low stirring speeds, leading to an imbalance between nucleation and growth rates, resulting in uneven particle size. At a stirring speed of 500 r / min, excessive shearing causes crystal breakage, and the particle size distribution shows obvious bimodalities and becomes wider. Ultimately, 300 r / min was selected as the subsequent process condition.
[0026] Table 1. Experimental results at different stirring speeds
[0027] Example 3 Based on Example 2, the effect of cooling rate on γ-aminobutyric acid crystallization was investigated. The effect of cooling rate on particle size distribution was studied under the following conditions: stirring speed 300 r / min, ultrasonic power 24.4 W / L, ultrasonic 3s pause 12s, and aging time 90 min. Table 2 and Figure 3 The particle size and distribution of crystals under different cooling rates are shown.
[0028] The experimental results for different cooling rates are shown in Table 2. From Table 2 and... Figure 3 It can be seen that with the increase of cooling rate, the Dv50 of the product crystals tends to decrease, while DS tends to increase, and the particle size distribution becomes wider. This is because when the cooling rate increases, the nucleation rate is much faster than the crystal growth rate, and a large number of crystal nuclei compete for growth resources, thus limiting the growth of single crystals (reducing Dv50); at the same time, the asynchronous nature of nucleation and the uneven diffusion of solute amplify the differences in crystal size, resulting in a wider particle size distribution (increasing DS), which is essentially a manifestation of the competition between nucleation and growth kinetics. Taking all factors into consideration, 0.5℃ / min was chosen as the condition for subsequent experimental studies.
[0029] Table 2 Experimental results at different cooling rates
[0030] Example 4 Based on Example 3, the effect of ultrasonic interval time on γ-aminobutyric acid crystallization was investigated. To avoid localized overheating caused by continuous ultrasound, an intermittent ultrasound mode is adopted. The ultrasound working time and pause time are set; ultrasound pauses can prevent localized overheating, balance crystal breakage and growth, improve the utilization rate of cavitation effect, and optimize crystallization results.
[0031] Under the conditions of cooling rate of 0.5℃ / min, stirring speed of 300r / min, ultrasonic power of 24.4W / L, and aging time of 90min, the effects of five ultrasonic intervals and the absence of ultrasonication on particle size distribution and crystal integrity were investigated. Table 3 shows the particle size distribution and crystal integrity of the product under different ultrasonic intervals.
[0032] The experimental results for different ultrasonic time intervals are shown in Table 3. Table 3 shows that the crystal size decreases with increasing ultrasonic working time. However, after an ultrasonic interval of 4 seconds, the decrease in Dv50 is no longer significant. Furthermore, crystal breakage occurs with prolonged ultrasonic working time, indicating that excessively long ultrasonic working times lead to crystal breakage, producing fine fragments and widening the particle size distribution. Considering Dv50, DS, and crystal integrity, the time interval within the range of 2–4 seconds of ultrasonic operation followed by an 8–16 seconds pause is considered ideal. Therefore, this range is determined to be the optimal ultrasonic interval.
[0033] Table 3. Experimental results for different ultrasound intervals.
[0034] Example 5 Based on Example 4, the influence of ultrasonic power density was investigated. The effects of five ultrasonic power densities (19.4 W / L, 30.9 W / L, 40.5 W / L, 51.6 W / L, and 82.4 W / L) on the product crystals were investigated under the following conditions: ultrasonication for 3 seconds followed by a 12-second pause; stirring speed of 300 r / min; cooling rate of 0.5 °C / min; and aging time of 90 min. Lower power was not designed because excessively low power results in weak cavitation, which would not effectively disperse agglomerates or promote uniform nucleation. Furthermore, the existing power density of 19.4 W / L is already close to the lower functional limit; further reduction would lead to uncontrollable agglomeration and a wider particle size distribution, violating the process objectives. The effects of different ultrasonic power densities on crystal habit are as follows: Figure 4 As shown, when the ultrasonic power density is 19.4 W / L, the crystal morphology is intact and the surface is smooth; at 30.9 W / L, the crystal is smooth and without defects or obvious agglomeration; when the power density reaches 40.5 W / L, obvious small grains are attached to the crystal surface; when the power density increases to 51.6 W / L, the crystal edge is broken and the number of small grains on the surface increases; when the power density reaches 82.4 W / L, the crystal is severely broken and accompanied by a large number of fine crystal agglomerations.
[0035] As the ultrasonic power density increases, crystal fragmentation becomes more severe. When the ultrasonic power density exceeds 30.9 W / L, obvious small grains adhere to the crystal surface. Taking all factors into consideration, 20–30 W / L was selected as the condition for subsequent process research.
[0036] Example 6 The effect of aging time was investigated based on Example 5. The effects of different aging times on crystal habit were studied under the following conditions: ultrasonic power 24.4 W / L; ultrasonication 3 s pause 12 s; stirring speed 300 r / min; cooling rate 0.5 ℃ / min. The results are as follows: Figure 5 As shown, after 30 minutes, the crystal surface is not smooth, and small crystals adhere; after 60 minutes, the number of small crystals decreases, but the surface remains rough; after 90 minutes, the crystals are smooth and intact, with no obvious small crystals; there is no significant difference between 120 minutes and 90 minutes, and the number of small crystals does not increase. Due to the balance between dissolution and growth within the crystallizer, as the aging time increases, some small crystals are dissolved, and the crystals grow more fully. It can be seen from the figure that after 90 minutes, the crystal habit does not change much, and there are fewer small crystals, resulting in a smoother crystal surface. Considering the time cost, an aging time of 90 minutes was chosen.
[0037] Example 7 A method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid (GABA) crystallization, the specific steps of which are as follows: 1. Impurity removal, decolorization, and filtration: Decolorize the GABA-containing liquid, filter it, and collect the filtrate as the solution to be concentrated.
[0038] 2. Concentration: Place the filtrate in a crystallizer for evaporation and stirring concentration. The heating temperature is 70℃, the vacuum degree is 0.08MPa, and the stirring speed is 300r / min, until it is concentrated to near saturation.
[0039] 3. Ultrasonic-assisted crystallization: After the filtrate is concentrated to near saturation, the liquid is stirred at 300 r / min and ultrasonic assistance is activated. The ultrasonic probe is inserted to a depth of 1 / 3 below the surface of the crystal slurry, and the ultrasonic power is 24.4 W / L. The ultrasonic treatment is paused for 12 seconds after 3 seconds. Simultaneously, the crystals are evaporated and crystallized at a temperature of 70℃ and a vacuum of 0.08 MPa until the crystal precipitation rate reaches 50% (based on the volume of saturated filtrate). After evaporation is stopped, the crystals are cooled to 25℃ at a cooling rate of 0.5℃ / min. The ultrasonic and stirring effects are then stopped, and the crystals are aged for 90 minutes.
[0040] 4. Washing and Drying: Filter the mother liquor to obtain wet crystals, wash the crystals, and dry them to obtain GABA crystals. The obtained crystals have a particle size distribution span (DS) of 1.422 and a median particle size (Dv50) of 196.3 μm. There is no agglomeration, and the crystals are intact with smooth surfaces.
[0041] Example 8 The GABA crystals obtained after optimization using ultrasonic-assisted processing (Example 7) were characterized with those obtained without ultrasonic assistance (before optimization) (the method for obtaining crystals without ultrasonic assistance is described in patent CN120081754A). The GABA crystals obtained from the two methods were compared and analyzed using scanning electron microscopy (SEM), particle size analyzer, X-ray diffraction (XRD), and infrared spectroscopy (IR).
[0042] (1) Particle size analysis The particle size of GABA crystals before and after the optimization process was measured, and the particle size data before and after optimization are shown in Table 4.
[0043] As shown in Table 4 and Figure 6 As shown, before optimization: it exhibits a broad bimodal distribution (Dv50=587.8μm, DS=2.283); after optimization: it exhibits a narrow unimodal distribution (Dv50=196.3μm, DS=1.422); the particle size refinement exceeds 66%, and the distribution narrowing exceeds 35%.
[0044] Table 4 Comparison of granularity data before and after optimization
[0045] (2) X-ray powder diffraction (XRD) and infrared spectroscopy (IR) analysis The results are as follows Figure 7 , Figure 8 As shown, the positions of the characteristic peaks of XRD before and after ultrasonic optimization are consistent, and there is no difference in the IR absorption peaks, confirming that ultrasonic treatment only regulates the particle size, distribution and aggregation state of the crystals, without changing the crystal form and chemical structure.
[0046] (3) Scanning electron microscopy (SEM) analysis The morphology of GABA crystals before and after optimization was observed by SEM, and the results are as follows: Figure 9 As shown, before optimization: the crystals are broken and irregular in shape (severe agglomeration and particle adhesion); after optimization: the crystals are smooth and complete and the particles are dispersed (agglomeration is significantly suppressed and the narrowing of the distribution is clearly reflected).
[0047] The above-described embodiments are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made to the technical solutions of the present invention by those skilled in the art without departing from the spirit of the present invention should fall within the protection scope of the present invention.
Claims
1. A method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid (GABA) crystallization, comprising: removing impurities and decolorizing a γ-aminobutyric acid-containing solution; heating and stirring to concentrate it to near saturation; then performing ultrasound-assisted crystallization; cooling; aging; filtration to obtain coarse crystals; and finally washing and drying to obtain the target crystals. The specific steps are as follows: (1) Impurity removal and decolorization: The liquid containing γ-aminobutyric acid is removed and decolorized, and the filtrate is collected as the solution to be concentrated; (2) Heating and concentration: The filtrate is placed in a crystallizer and heated and stirred to concentrate it to near saturation; (3) Ultrasonic-assisted crystallization: When the filtrate is concentrated to near saturation, turn on ultrasonic-assisted crystallization, continue heating and stirring to evaporate until the crystal precipitation rate reaches 50% and stop evaporation. Then cool it to 20-25℃ at a cooling rate of 0.4-0.6℃ / min, stop ultrasonication and stirring, and continue aging for 60-120min to obtain crystal mother liquor. (4) Washing and drying: filter the mother liquor to obtain crude crystals, wash the crystals, and dry them to obtain γ-aminobutyric acid crystals.
2. The method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization according to claim 1, characterized in that: The heating and concentration conditions in step (2) and the heating, stirring and evaporation conditions in step (3) are: temperature 60-75℃, vacuum degree 0.07-0.09MPa, and stirring speed 250-450r / min.
3. The method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization according to claim 2, characterized in that: The heating and concentration conditions / heating and stirring evaporation conditions are: temperature 65-70℃, vacuum degree 0.08MPa, and stirring speed 300r / min.
4. The method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization according to claim 1, characterized in that: The cooling rate is 0.5℃ / min.
5. The method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization according to claim 1, characterized in that: In step (3), the aging time of the crystals after cooling is 90 minutes.
6. The method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization according to claim 1, characterized in that: The conditions for ultrasonic-assisted crystallization in step (3) are: ultrasonic power density of 20-30 W / L, ultrasonic probe inserted to a depth of 1 / 3-1 / 2 below the surface of the crystal slurry, and intermittent ultrasonic mode.
7. The method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization according to claim 6, characterized in that: The ultrasonic power density is 24.4 W / L.
8. The method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization according to claim 6, characterized in that: The intermittent ultrasound mode involves pausing for 8 to 16 seconds after each ultrasound session of 2 to 4 seconds.
9. The method for controlling the particle size of ultrasound-assisted γ-aminobutyric acid crystallization according to claim 6, characterized in that: The ultrasonic probe is inserted to a depth of 1 / 3 below the surface of the crystal slurry, and an intermittent ultrasonic mode is used, with a 12-second pause after every 3 seconds of ultrasonic waves.
Citation Information
Patent Citations
Method for separating and purifying gamma-aminobutyric acid from whole cell or enzymatic conversion liquid
CN120081754A
Crystallization method for preparing triaminoguanidine nitrate crystal with narrow particle size distribution and triaminoguanidine nitrate crystal
CN108623499A
Process for solventing-out, cooling, mixing and crystallizing pentamethylene diamine hydrochloride
CN116178173A
Palm oil fractionation process based on fat crystal number and particle size control
CN117186988A
Method and device for crystallizing gamma-aminobutyric acid
CN117771724A
Cited By
Intelligent control method and system for separation and purification of D (-)-tartaric acid
CN121432902A